The Priorities of Socio-Economic and Financial Development of the North Caucasus Federal District in the Current Geopolitical Situation - Akinin, Petr; Akinina, Valentina; Alimova, Inna; Viderker, Natalya; Ter-Akopov, Aleksandr (International Review of Management and Marketing, 2016)
The aim of the research is to establish the priorities of the socio-economic and financial development of the North Caucasus macro-region within the boundaries of the federal district in the current geopolitical situation. The results of the research show in details the priorities of socio-economic and financial development of the North Caucasus Federal District in terms of import substitution and finance rationalization under the current financial crisis and international sanctions against the Russian Federation. It is a well-known fact that more than 30 nations declared this territory the area of their strategic interests. The Caucasus became the subject of so-called “pipe wars”; it also became “a buffer zone” in the distribution of the Islamic state model. We have a new strategy of working with migrants in the Islamic regions of Russia (Gabdrafikov et al., 2015). Previously, the Caucasus region has been the outcome for migrants, but today it has become to develop new models for the socio-economic attractiveness of the region (Karepova et al., 2015). Statistical, monographic, sociological methods as well as logical modelling have been used in the research. Keywords: sanctions, strategy, cluster, import substitution JEL Classifications: F51; L12